Community-level environmental projects as learning tools for planners: a case study of graduate planning students. Issue 3 (16th March 2017) - Portman, Michelle E.; Teff-Seker, Yael
Abstract : Despite the potential environmental impact of urban planning, there is little research on Environmental Education (EE) in the context of urban planning curricula. This study follows graduate planning students' learning experience during group projects assigned as part of a planning course at the Technion – Israel Institute of Technology. These participatory projects, characterized as project-based learning and service learning, took place in several communities in Israel. We examined the types of learning impacts the projects engendered by analyzing the reported experiences of the students using parameters from the field of EE. The main goal of this research is to understand the contribution of such practical, hands-on project exercises to the course curriculum for inculcating environmental education themes. Findings indicate that projects helped students acquire and/or improve professional tools. They enhanced motivation to consider environmental concerns in their work and in some cases changed students' personal environmental behavior.